Pengaruh Efektivitas Pengendalian Internal, Love of Money, Religiusitas Terhadap Kecurangan Pengelolaan Dana Desa Se-Kecamatan Pupuan Kabupaten Tabanan - Utpatti, Ni Nyoman Dewi Sanistyawati; Sumadi, Ni Komang; Andayani W, Rai Dwi (UNHI Press, 2025)
A village, according to Law Number 6 of 2014, is a legal community unit with territorial boundaries that has the authority to regulate and manage government affairs and community interests based on the rights of origin and traditions recognized in the Indonesian government system. The Village Government, led by the Village Head and assisted by village officials, is responsible for managing village finances, including Village Funds which are sourced from the APBN and used for governance, development, guidance and community empowerment. Village financial management is regulated in Minister of Home Affairs Regulation Number 20 of 2018 and Number 73 of 2020, and the use of Village Funds is regulated by Village Minister Regulation Number 7 of 2023. The planning process to accountability of the APBDes is carried out by the Village Head together with village officials and involves the Village Consultative Body (BPD). Even though there is a detailed internal control system, irregularities or fraud still occur in village financial management, especially the Village Fund, which involves data manipulation, asset theft, or violations of business ethics. This research is quantitative research by testing hypotheses on the influence of independent variables, namely Internal Control Effectiveness, Love of Money, Religiosity, which influence the dependent variable, namely Fraud. The population in this study was all village officials including the Village Head, Village Secretary, Village Technical Executive and Village Regional Executive, along with all members of the Village Consultative Body (BPD) in villages throughout Pupuan District, Tabanan Regency, totaling 330 people. The nuumber of sampeles in this studiy was 126 using the Purposive Sampling and tested using multiple linear regresion analiysis technques. Based on research, The effectiveness of internal control and religiosity have a negative and significant effect on fraudulent management of village funds, while love of money has no effect on fraudulent management of village funds.